Quantification of Skeletal Muscle at the First Lumbar Level for Prognosis in Amyotrophic Lateral Sclerosis - Yujia Cao; Baoyu Yuan; Xiuyu Jiang; Chunming Xie; Di Wu; Zhijun Zhang (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Skeletal muscle parameters at the first lumbar vertebra (L1) level on computed tomography (CT) are common indicators for muscle mass. However, their relationship with the severity and prognosis of amyotrophic lateral sclerosis (ALS) patients remains unclear. Methods This cohort study included ALS patients who underwent chest CT scans between January 2018 and January 2022 and healthy controls (HCs) matched for gender and age. Overall survival (OS) was determined from the date of chest CT to death, tracheal intubation or 1 January 2024. Using ImageJ software, skeletal muscle area and density (L1 SMA/SMD), skeletal muscle index (L1 SMI), paraspinal muscle area and density (L1 PMA/PMD) and subcutaneous fat area and density (L1 SFA/SFD) at L1 were quantified. The relationships between the quantified muscle parameters and both King's clinical stages and the Revised ALS Functional Rating Scale (ALSFRS‐R) were analysed. The Cox proportional hazard model was used to evaluate the hazard ratio (HR) of skeletal muscle parameters as risk factors for outcome events, and to construct a nomogram. Results Muscle parameters in ALS patients (n = 102; 36.27% female; mean age, 60.85 ± 10.58 years) were significantly lower compared with HCs (p < 0.001). L1 SMD (p = 0.047) and L1 PMD (p = 0.003) both differed significantly across the King's clinical stages. ALSFRS‐R scores correlated with L1 SMA (r = 0.35, p < 0.001), L1 SMI (r = 0.34, p < 0.001), L1 PMA (r = 0.27, p = 0.007) and L1 PMD (r = 0.27, p = 0.007). Multivariate Cox regression analysis revealed that L1 SMA (HR = 0.96, 95% confidence interval [CI] = 0.94–0.98, p = 0.001), L1 SMD (HR = 0.92, 95% CI = 0.88–0.96, p < 0.001) and L1 PMA (HR = 1.06, 95% CI = 1.01–1.11, p = 0.022) significantly influenced ALS survival, with area under the curves (AUCs) of 0.687 and 0.851 for 1‐ and 3‐year OS prediction. The consistency index (C‐index) for the nomogram was 0.72 (95% CI = 0.641–0.793). Conclusions Skeletal muscle parameters at L1 level on CT are significantly associated with clinical severity and prognosis in ALS. Trial Registration Chinese Clinical Trial Registration Center: ChiCTR230078702